EKUMENICZNY ASPEKT USPRAWIEDLIWIENIA MARYI I JEJ „ZASŁUG” - Lipniak, Jarosław (Studia Oecumenica, 2014)
The issue of justification of Mary and her merits has been distinguishing the Christians for ages. Both issues are serious difficulty in driving for achievement of visible unity of Christ’s disciples. History of the Church shows that dogmas defined at the Councils were rather starting point than an end of interpretation of Revelation in the Church. In the patristic period of time not only the theologians but the whole Church as well was taking part in arriving to proper interpretation of the faith. Mary needed God’s mercy and has granted to this mercy in more perfect way, not ordinary as a rest of Eve’s children. She has granted to the justification beforehand, not subsequently. She was protected against the original sin, and not relieved from it. The justification of Mary is of preventive character. The Christ is, in relation to her, more perfect Mediator, because keeps her from the sin, instead – like in a case of the other Adam’s descendants – to clear of the sin.